Telemonitoring for the Management of Patients with Heart Failure - Ferdinando Iellamo; Barbara Sposato; Maurizio Volterrani (Cardiac Failure Review)
Advances in technology now make it possible to manage heart failure (HF) from a remote to a telemonitoring approach using either noninvasive solutions or implantable devices. Nowadays, it is possible to monitor at-home parameters that can be recorded, stored and remotely transmitted to physicians, allowing them to make decisions for therapeutic modification, hospitalization or access to the emergency room. Standalone systems are available that are equipped with self-intelligence and are able to acquire and elaborate data that can inform the remote physician of impending decompensation before it results in additional complications. The development of miniature implantable devices, which could measure haemodynamic variables and transmit them to a monitor outside the body, offers the possibility for the physician to obtain more frequent evaluations of HF patients and the opportunity to take these data into account in management decisions. At present, several telemonitoring devices are available, but the only Food and Drug Administration-approved system is the cardio-microelectromechanical system, which is an implantable pulmonary arterial pressure (PAP) monitoring device that allows a direct monitoring of the PAP via a sensor implanted in the pulmonary artery. This information is then uploaded to a web-based interface from which healthcare providers can track the results and manage patients. At present, the challenge point for telemedicine management of HF is to find the more relevant biological parameter to monitor the clinical status.